ChemInform Abstract: SmI2‐Mediated Couplings of α‐Amino Acid Derivatives. Formal Synthesis of (—)‐Pumiliotoxin 251D and (.+‐.)‐Epiquinamide. Issue 37 (22nd August 2013) - Pinho, Vagner D.; Procter, David J.; Burtolosco, Antonio C. B.
Abstract A straightforward approach for the construction of hydroxylated indolizidine, quinolizidine and piperidine systems via highly diastereoselective SmI2‐mediated coupling reactions of α‐amino acid derivatives with methyl acrylate is developed.